LIMITATION ON THE MASS EXCHANGE BETWEEN THE UPPER AND LOWER MANTLE: THE EVOLVING CONVECTION REGIME OF THE EARTH - Allegre C.J. (My University, 1997)
It is increasingly accepted, through the use of geochemical arguments, that the Earth's mantle has a two-layer structure, comprising an upper and lower mantle. Estimates of the exchange of matter and energy between these two layers are, thus, central to understanding the dynamics of the Earth.Geochemical mass balance permits us to estimate the average flux of exchange between the lower and upper mantle. This estimate can be made using two different classes of chemical tracers: the LiL isotopic systems and the rare gas isotopic system. The absolute values and comparison between these tracers argues for:1. a limited exchange rate between the lower and upper mantle, the average rate over 4.5 x 109 yr being less than 10% of the present-day subduction rate, S.;2. from comparison of these values with the seismic evidence of slab penetration, two-layer convection having operated for most of the Earth's history, but whole mantle convection having started less than 1 billion years ago. We are presently in a transitional stage between these two modes of operation.
Keywords: MASS EXCHANGE; TWO-LAYER MANTLE